A Statistical analysis on Vishay Philippines, Inc. DOE - Balucan, John Paul (College of Engineering, 2001)
Vishay Philippines, Inc. is conducting a design of experiments on infrared receiver modules, one of its numerous product lines. The company has been continuously conducting DOEs to improve the performance characteristics of the IR module and to lower its rejection rate. Data from a previous DOE was given to the group for statistical analysis. From problem analysis, the group was able to identify the weak wire bonding as the most important root cause of the rejection of the IR modules. Several factors affect the manufacture of the IR modules and these factors were the ones considered for the DOE. Factors identified were Ball Force, Ball power, Wedge Width, Wedge power, Ball resistance, Peel resistance, Wedge Width, wedge length, ball size diameter and ball size resistance. The design of experiments conducted is 2k design because there exists 2 levels for each of the factors. From the data given by the company, it appears that, after using the normal probability plot and ANOVA, factor B which is ball power, is a significant factor. The group believes that a 2k design must be used for statistical analysis. However, due to the costs incurred in conducting a full 2k factorial experiment, a 2 5-2 is recommended. For the data to be accurate the 2k designs should be done properly so that proper treatment combinations be identified and this would take into consideration that higher order interactions of the design. In doing so, it can be determined whether or not these interactions are significant. Also, as an area of further study, temperature, wire type and age of the machines can be reviewed for their contributions to error or defects.